Correlation Between Level of Knowledge And Tooth Brushing Practices With Oral Hygiene Among Elementary School Students - Auditra, Farhan; Rosidi, Ali; Sholekhah, Nur Khamilatusy (Odonto : Dental Journal, 2025)
Background: Poor oral health has a significant impact on a person's quality of life, as seen in Ministry of Health data, especially in Semarang City which recorded an increase in cases from year to year. Children aged 10-12 years are at high risk due to lack of knowledge and poor oral hygiene behavior, such as brushing tooth properly and correctly has been proven to be effective in preventing plaque, calculus, and other periodontal diseases. One way to assess the level of oral and dental hygiene is to use the Simplified Oral Hygiene Index (OHI-S). This study aim to analyze the correlate between the level of knowledge of oral health and tooth brushing practices on the oral hygiene of grade V students of SD Islam Tunas Harapan Semarang.Method: This study uses an observational study, namely a cross-sectional study approach. The population was 111 grade V students at Islamic Elementary Shool Tunas Harapan Semarang. The sample was 82 children using the total sampling technique. Data were obtained from questionnaires filled out by students, observation sheets, and oral hygiene assessment sheets.Result: The data were analyzed using the Spearman test. The value significant was ρ=0.000 (ρ<0.05) for the knowledge level and oral hygiene in children and the significant value was ρ=0.000 (ρ<0.05) for the tooth brushing practice and oral hygiene in children.